Facilitation alters climate change risk on rocky shores. Issue 2 (20th December 2021) - Jurgens, Laura J.; Ashlock, Lauren W.; Gaylord, Brian
Abstract: A huge fraction of global biodiversity resides within biogenic habitats that ameliorate physical stresses. In most cases, details of how physical conditions within facilitative habitats respond to external climate forcing remain unknown, hampering climate change predictions for many of the world's species. Using intertidal mussel beds as a model system, we characterize relationships among external climate conditions and within‐microhabitat heat and desiccation conditions. We use these data, along with physiological tolerances of two common inhabitant taxa (the isopod Cirolana harfordi and the porcelain crab Petrolisthes cinctipes ), to examine the magnitude of climate risk inside and outside biogenic habitat, applying an empirically derived model of evaporation to simulate mortality risk under a high‐emissions climate‐warming scenario. We found that biogenic microhabitat conditions responded so weakly to external climate parameters that mortality risk was largely unaffected by climate warming. In contrast, outside the biogenic habitat, desiccation drove substantial mortality in both species, even at temperatures 4.4–8.6°C below their hydrated thermal tolerances. These findings emphasize the importance of warming‐exacerbated desiccation to climate‐change risk and the role of biogenic habitats in buffering this less‐appreciated stressor. Our results suggest that, when biogenic habitats remain intact, climate warming may have weak direct effects on organisms within them. Instead, risk to such taxa is likely to be indirect and tightly coupled with the fate of habitat‐forming populations. Conserving and restoring biogenic habitats that offer climate refugia could therefore be crucial to supporting biodiversity in the face of climate warming.